World Bank East Asia and Pacific Economic Update 2011, Volume 2 : Navigating Turbulence, Sustaining Growth - World Bank (Washington, DC, 2013)
Growth in developing East Asia in the first half of 2011 remained strong, but continued to moderate, mainly due to weakening external demand. Global growth was also affected by supply shocks from geopolitical disturbances in the Middle East, supply chain disruptions following the earthquake and tsunami in Japan, and a slower-than-expected recovery of private demand in crisis-affected countries. More recently, uncertainties over fiscal sustainability in the U.S. and sovereign debt in the Euro zone fed financial volatility and affected investor and consumer sentiment. Domestic demand in East Asian economies has also been softening, driven by the normalization of fiscal and monetary policy, although it remained robust and the largest contributor to growth. We project that real Gross Domestic Product(GDP) in developing East Asia will increase by 8.2 percent in 2011 (4.7 percent excluding China), while growth will slow to 7.8 percent in 2012. Risks are on the downside, however. Based on the still robust current growth projections, the proportion of people living on less than US$2 a day in developing East Asia is expected to decrease to about 24 percent in 2011, down two percentage points from 2010, and an estimated 38 million people are projected to move out of poverty. However, poverty reduction efforts would be hampered in the event of another sudden increase in food prices against a backdrop of slowing income growth. In the short- to medium-term, East Asia's growth prospects are constrained by global uncertainty and by the impact of natural disasters. The slow progress towards resolution of debt problems in the Euro zone intensified investors' concerns over global growth and stability. As capital flowed out of emerging markets into relatively safer havens, portfolio investments reversed and stock markets lost value in East Asia. Markets remain jittery, even after the Euro zone countries agreed on a solution for the sovereign debt and banking problems. Fiscal and financial consolidation in the Euro zone is likely to reduce growth in Europe, and could lead to renewed financial outflows from East Asia as banks shore up their capital coverage. Credit outstanding from European banks to developing East Asia amounts to US$427 billion, or six percent of GDP. But high reserves and current account surpluses protect most East Asian countries against the impact of possible renewed financial stress.